2022
DOI: 10.1088/1361-6463/ac74f7
|View full text |Cite
|
Sign up to set email alerts
|

Surface-induced gas-phase redistribution effects in plasma-catalytic dry reforming of methane: numerical investigation by fluid modeling

Abstract: Plasma catalysis is an emerging process electrification technology for industry decarbonization. Plasma-catalytic dry reforming of methane (DRM) relies on the mutual effects of the plasma and the catalyst leading to the higher chemical conversion efficiency. The effects of catalyst surfaces on the plasma are predicted to play a major role, yet they remain unexplored. Here, a 1D plasma fluid model combined with 0D surface kinetics is developed to reveal how the surface reactions on platinum (Pt) catalyst affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…225 This study highlighted that the catalyst could affect the spatial distributions of active species, thereby influencing the plasma chemistry indirectly. 225 An experimental study from the Nozaki group 207,226 investigated the electronic changes in Ni/Al 2 O 3 for DRM. As shown in Figure 19, the Ni was partially oxidized to NiO up to a 20 μm depth after CO 2 plasma treatment, due to the strong oxidation ability of electron-impact excited CO 2 and NTP heating effects via a plasma-mediated Eley−Rideal mechanism.…”
Section: Gliding Arc (Ga)mentioning
confidence: 95%
See 1 more Smart Citation
“…225 This study highlighted that the catalyst could affect the spatial distributions of active species, thereby influencing the plasma chemistry indirectly. 225 An experimental study from the Nozaki group 207,226 investigated the electronic changes in Ni/Al 2 O 3 for DRM. As shown in Figure 19, the Ni was partially oxidized to NiO up to a 20 μm depth after CO 2 plasma treatment, due to the strong oxidation ability of electron-impact excited CO 2 and NTP heating effects via a plasma-mediated Eley−Rideal mechanism.…”
Section: Gliding Arc (Ga)mentioning
confidence: 95%
“…However, the production of vibrationally excited CH 4 and CO 2 is the dominant reaction pathway at E/ N < 700 Td, compared to the dissociation and ionization rates (see Figure 17). 207 Zhu et al 225 investigated the surface-induced gas-phase redistribution in plasma-catalytic DRM using 1D plasma fluid model combined with 0D surface kinetics. The authors reported that surface reaction changes the development of electron avalanches in the plasma phase, resulting in an improved spatial inhomogeneity.…”
Section: Gliding Arc (Ga)mentioning
confidence: 99%
“…This is mainly due to the lack of gas-phase reaction products and their surface reaction rates, which limit further studies on surface reactions. Furthermore, it has been shown that the catalytic Al O 2 3 surface does not affect the product density by more than 10% [92] even in packed-bed DBD, which is When the input power is 500 mW, the voltage and current waveforms of TEOS/Ar discharge without O 2 are shown in Figure 3a. The discharge is stable and repeatable, and the discharge occurs at the rising edge of the pulse voltage.…”
Section: Netural Speciesmentioning
confidence: 99%
“…This is mainly due to the lack of gas‐phase reaction products and their surface reaction rates, which limit further studies on surface reactions. Furthermore, it has been shown that the catalytic Al2normalO3 surface does not affect the product density by more than 10% [ 92 ] even in packed‐bed DBD, which is equivalent to a 0.3 mm gap. The catalyst has more active sites than raw Al2normalO3.…”
Section: Chemical Kineticsmentioning
confidence: 99%
“…The CO 2 -CH 4 NRP were modelled with 1D Ćuid model in [22], whose kinetic scheme was modiĄed in [23] to take into account surface processes. Another 1D Ćuid model taking into account catalytic surfaces and spatial inhomogeneity has been developed in [24] to model a cylindrical packed-bed DBD reactor. Finally, [25] recently developed an neural network based model of a CO 2 -CH 4 nanosecond pulsed dielectric barrier discharge to predict the conversion, energy efficiency and selectivity of the discharge, but does not relies on a chemistry set.…”
Section: Introductionmentioning
confidence: 99%